Optimalisasi Rute untuk Meminimalkan Biaya Pengangkutan Sampah di Kota Jember menggunakan Metode Saving Matrix oleh Dinas Lingkungan Hidup Kabupaten Jember - Eka Bambang Gusminto; Rila Putri Lesmana (Universitas Jember, 2023)
This study aims to analyze the determination of the distance and route for the implementation of waste transportation by the Environmental Service of Jember Regency. This research was conducted in 3 administrative sub-districts, namely Kaliwates, Patrang, and Sumbersari sub-districts using the Saving Matrix method. By using the Saving Matrix method, the best solution will be found that can optimize the closest route that can be applied to minimize the cost of transporting waste in the City of Jember. The method starts by determining the Distance Matrix so that later it will be found the Savings matrix. After that, the TPS points are combined into a Saving Matrix route so that a new route will be obtained with a more minimal distance and fuel cost. In this study, it is assumed that 1 liter of diesel can cover a distance of 8 km. The results of this study indicate that the results of research using the saving matrix method can optimize the route to minimize costs by 36.51%, while the fuel cost saved is Rp. 4.016.691,-. This shows that route optimization using the Saving Matrix method can minimize routes and costs for transporting waste by the Jember Environmental Department. Keywords: Saving Matrix, Optimization, Transportation